Ferrocenyl-substituted tetrahydrothiophenes via formal [3 + 2]-cycloaddition reactions of ferrocenyl thioketones with donor–acceptor cyclopropanes - Mlostoń, Grzegorz; Kowalczyk, Mateusz; Augustin, André U.; Jones, Peter G.; Werz, Daniel B. (Beilstein Journal of Organic Chemistry, 2020)
Ferrocenyl thioketones reacted with donor–acceptor cyclopropanes in dichloromethane at room temperature in the presence of catalytic amounts of Sc(OTf)3 yielding tetrahydrothiophene derivatives, products of formal [3 + 2]-cycloaddition reactions, in moderate to high yields. In all studied cases, dimethyl 2-arylcyclopropane dicarboxylates reacted with the corresponding aryl ferrocenyl thioketones in a completely diastereoselective manner to form single products in which (C-2)-Ar and (C-5)-ferrocenyl groups were oriented in a cis-fashion. In contrast, the same cyclopropanes underwent reaction with alkyl ferrocenyl thioketones to form nearly equal amounts of both diastereoisomeric tetrahydrothiophenes. A low selectivity was also observed in the reaction of a 2-phthalimide-derived cyclopropane with ferrocenyl phenyl thioketone.
Keywords: [3 + 2]-cycloaddition reactions; donor–acceptor cyclopropanes; ferrocenyl thioketones; sulfur heterocycles; tetrahydrothiophenes

(untitled) - Benetti, S.; De Risi, C.; Pollini, G. P.; Zanirato, V. (Chem. Rev., 2012)

(untitled) - De Clercq, P. J. (Chem. Rev., 1997)

(untitled) - Huisgen, R.; Fulka, C.; Kalwinsch, I.; Xingya, L.; Mloston, G.; Moran, J. R.; Pröbstl, A. (Bull. Soc. Chim. Belg., 1984)

(untitled) - Mlostoń, G.; Heimgartner, H. (Pol. J. Chem., 2000)

1,3-Dipolar cycloaddition chemistry towards heterocycles and natural products - Mlostoń, G.; Heimgartner, H. (Wiley, 2002)

(untitled) - Huisgen, R.; Mlostoń, G.; Giera, H.; Langhals, E. (Tetrahedron, 2002)

(untitled) - Huisgen, R.; Mloston, G.; Langhals, E. (J. Org. Chem., 1986)

(untitled) - Huisgen, R.; Mlostoń, G.; Langhals, E.; Oshima, T. (Helv. Chim. Acta, 2002)

(untitled) - Augustin, A. U.; Sensse, M.; Jones, P. G.; Werz, D. B. (Angew. Chem., Int. Ed., 2017)

(untitled) - Augustin, A. U.; Merz, J. L.; Jones, P. G.; Mlostoń, G.; Werz, D. B. (Org. Lett., 2019)

(untitled) - Kowalski, K.; Karpowicz, R.; Mlostoń, G.; Miesel, D.; Hildebrandt, A.; Lang, H.; Czerwieniec, R.; Therrien, B. (Dalton Trans., 2015)

(untitled) - Hejmanowska, J.; Jasiński, M.; Mlostoń, G.; Albrecht, Ł. (Eur. J. Org. Chem., 2017)

(untitled) - Mlostoń, G.; Hamera-Fałdyga, R.; Linden, A.; Heimgartner, H. (Beilstein J. Org. Chem., 2016)

(untitled) - Mlostoń, G.; Hamera-Fałdyga, R.; Jeske, M.; Godziszewska, M.; Urbaniak, K.; Heimgartner, H. (J. Sulfur Chem., 2018)

(untitled) - Mlostoń, G.; Urbaniak, K.; Zimmer, R.; Reissig, H.-U.; Heimgartner, H. (ChemistrySelect, 2018)

(untitled) - Astruc, D. (Eur. J. Inorg. Chem., 2017)

(untitled) - Heinze, K.; Lang, H. (Organometallics, 2013)

(untitled) - Mlostoń, G.; Hamera-Fałdyga, R.; Celeda, M.; Heimgartner, H. (Org. Biomol. Chem., 2018)

(untitled) - Mloston, G.; Hamera-Fałdyga, R.; Heimgartner, H. (J. Sulfur Chem., 2018)

(untitled) - Petzold, M.; Jones, P. G.; Werz, D. B. (Angew. Chem., Int. Ed., 2019)

(untitled) - Augustin, A. U.; Busse, M.; Jones, P. G.; Werz, D. B. (Org. Lett., 2018)

(untitled) - Cai, Z.-J.; Liu, C.-X.; Wang, Q.; Gu, Q.; You, S.-L. (Nat. Commun., 2019)

(untitled) - Gröber, S.; Matczak, P.; Domagała, S.; Weisheit, T.; Görls, H.; Düver, A.; Mlostoń, G.; Weigand, W. (Materials, 2019)

(untitled) - Reissig, H.-U.; Zimmer, R. (Chem. Rev., 2003)

(untitled) - Schneider, T. F.; Kaschel, J.; Werz, D. B. (Angew. Chem., Int. Ed., 2014)

(untitled) - Cavitt, M. A.; Phun, L. H.; France, S. (Chem. Soc. Rev., 2014)

(untitled) - Werz, D. B.; Biju, A. T. (Angew. Chem., Int. Ed., 2020)

(untitled) - Kreft, A.; Lücht, A.; Grunenberg, J.; Jones, P. G.; Werz, D. B. (Angew. Chem., Int. Ed., 2019)

(untitled) - Mlostoń, G.; Hamera, R.; Heimgartner, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2015)

(untitled) - Mlostoń, G.; Pipiak, P.; Heimgartner, H. (Beilstein J. Org. Chem., 2016)

(untitled) - Rodriquez-Cendejas, C. D.; Liebeskind, L. S.; Peña-Cabrera, E. (ARKIVOC, 2005)